Prototyping antarmuka Web Cybers Academy melalui Integrasi Desain untuk Meningkatkan Efektivitas Pengguna - Cecelya, Zary; Rahmadi, Agyl Ardi; Armin, Aidil Primasetya (Jurnal Ilmu Siber dan Teknologi Digital, 2024)
Purpose: This study aims to develop a prototype for an integrated Cyber Academy e-learning web interface, enhancing effectiveness and user experience by combining its Learning Management System (LMS) and Project Management System (PMS). Methodology/approach: Using Design Thinking, the research began with empathy (interviews and surveys with students and teachers). After defining the problems, the Ideate phase focused on a unified interface design. Prototype development followed, and the prototype was rigorously tested with users via the System Usability Scale (SUS) method to evaluate usability and satisfaction. Results: Based on 49 respondents, the prototype achieved a SUS score of 79.75, categorized as "A" (excellent and acceptable usability). User feedback also indicated areas for future refinement Conclusions: This study successfully developed a highly usable and satisfying integrated e-learning web interface. Design Thinking was effective in creating a more functional, user-centred platform. Limitations: The study was limited to Figma prototype development and usability testing with registered Cyber Academy users, primarily from one institution; actual system implementation and broader testing were beyond the scope. Contribution: This study offers a practical framework for integrating e-learning and project management systems using Design Thinking, providing insights for Cybers Academy to improve its platform and serving as a case study for similar educational integration challenges.